Identity of subjectivity in ethical discourse - Bacevičiūtė, Danutė (Religija ir kultūra, 2009)
This article deals with the problem of the ethical discourse, specifically with the manner in which ethical discourse describes identity of subjectivity. The positions of Immanuel Kant and Emmanuel Levinas are being analysed to this end. Both philosophers give precedence to the ethical over the theoretical. However, despite this common feature, these positions radically diverge when they describe identity of ethical subjectivity. Kantian grounding of ethics appeals to the autonomous will of the subject, whereas Levinasian ethical relationship emerges with the Other’s demand. Thus in one case there was postulated “firm” identity of subjectivity, in another – vulnerable subjectivity without identity. The question is: whether the extremeness of these positions not turns into the peculiar pathology or aesthetical perversity which is perceived as obstacle for the ethical? The article makes attempt to find an alternative to the opposition of identity and alterity. The description of concrete relation with another person enables us to speak about oneself as another.
Keywords: Kant; Levinas; identity of subjectivity; alterity; oneself as another